2014
DOI: 10.3171/2013.11.focus13483
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of microscope-integrated intraoperative fluorescein videoangiography during arteriovenous malformation surgery: preliminary results

Abstract: Object The authors report on the use of a recently developed microscope-integrated fluorescent module using low-dose intravenous fluorescein for videoangiography during arteriovenous malformation (AVM) surgery. Methods The authors analyzed the application of a low-dose intraoperative fluorescein in 4 consecutive patients undergoing AVM surgery. The ability to distinguish the associated vessels of the AVM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Post-resection FLOW 800 analysis demonstrates that the primary vein is now blue (D). Our team has also used fluorescein in place of the ICG and has found reasonable results similar to those of the ICG (41,42). The advantage of fluorescein over ICG is that the dye can be visualized through the microscope's binoculars (Figure 2) (43).…”
Section: Surgical Pearlsmentioning
confidence: 76%
“…Post-resection FLOW 800 analysis demonstrates that the primary vein is now blue (D). Our team has also used fluorescein in place of the ICG and has found reasonable results similar to those of the ICG (41,42). The advantage of fluorescein over ICG is that the dye can be visualized through the microscope's binoculars (Figure 2) (43).…”
Section: Surgical Pearlsmentioning
confidence: 76%
“…The arterial phase appears early when used in a patient with an abnormal connection between the venous and arterial circulations, such as a DAVF or AVM, where the blood flow is aberrantly fast. The arterial phase was reported to be 11 s in a case report of a DAVF (34) and 10–15 s in AVM surgeries (13, 16, 18, 23) after IV FNa injection. These durations are shorter than those reported during IV FNa videoangiography in aneurysm surgeries, in which the arterial phase typically appears for more than 20 s (20, 22, 31, 32).…”
Section: Phases Of Fna Videoangiography and Factors That Affect Phasesmentioning
confidence: 98%
“…Wrobel et al (32) reported a case of high-dose FNa videoangiography using 2,000 mg IV bolus. In other neurosurgical reports, IV doses range from 75 mg to 500 mg per bolus (6, 18–21, 30, 31, 33) or from 1 mg/kg to 1.5 mg/kg per body weight (16, 34).…”
Section: Dosages Of Fna For Vascular Applicationsmentioning
confidence: 99%
“…Wide-field fluorescence imaging has the advantage of improved field of view with immediate visual feedback to the surgeon, which has exploited such fluorophores as PpIX, 32,33,96,102,116,127,130–133,136,148,153–156 ICG, 29,44,63,85 and fluorescein. 1,22,23,65,71,74–76,92,98,111,112,124,125,128 For example, ALA-PpIX fluorescence provides the surgeon with immediate visualization of a tumor, noting areas with significant PpIX accumulation as a red-pink fluorescence and areas without significant visible levels of fluorescence with a violet-blue background from the excitation light. Current PpIX microscope-based work in mostly high-grade gliomas report sensitivities as low as 20%–30%, specificities > 90%, and overall accuracies 70%–90%.…”
Section: Fluorescencementioning
confidence: 99%